Arabic Students’ Perception of the Roles of Arabic Education in Sustainable Development in Kwara State, Nigeria - Abdullahi, M. S.; Abdullahi, M. S. (Kashere Journal of Education, 2021)
Language is the parameter for effective communication in a multi-cultural and multi-lingual society. Language has contributed massively in turning the world into a global village and as well plays a significant role in the formation and upholding national and international values. Arabic as a language plays a prominent role in the facilitation and promotion of inter-cultural communication and sustainable development. This study investigated the perception of Arabic students on the roles of Arabic education in sustainable development in Kwara State, Nigeria. Arabic students in the study consisted of all undergraduates and postgraduates in the state. These groups of students constituted the population for the study. 270students were sampled using a purposive sampling technique. Researcher’s designed questionnaire was used to elicit information from the respondents. The instrument was validated by three experts in Arabic Education, Measurement and Evaluation and yielded a co-efficient of 0.72 when subjected to a test-retest reliability procedure through the Pearson Product Moment Coefficient. The data collected was analyzed with the percentage, t-test and Analysis of Variance (ANOVA) at 0.05 alpha level. Findings from the study revealed that Arabic students held positive perception on the role of Arabic education in sustainable development. The study recommended that multilingual education (which embeds Arabic Education) should be encouraged and promoted across the nation via the re-branding of language education policy. This could help to promote the role of Arabic education in the national sustainable development.